Factors Affecting the Competitive Reduction of 8,8-Dimethylnaphthalene-1,4, 5(8h)-Trione in a Diels-Alder Cycloaddition with Hydroxysulfinyldienes - Caroli-Rezende, M; Almodovar-Fajardo, I (Springer Verlag, 2014)
Competing reduction and cycloaddition products were formed in the reaction of 8,8-dimethylnaphthalene-1,4,5(8H)-trione with a hydroxysulfinyldiene. The ratio of reduction to cycloaddition products depended on the stereochemistry of the diene and on the solvent employed, being higher in ethanol than in benzene. The ratio was also affected by the addition of Lewis acids, decreasing in the order BF3 = Al2O3 > MgCl2 > ZnCl2. The results help to explain and predict the occurrence of these competing processes in Diels-Alder cycloadditions involving quinonedienophiles. © 2013 Iranian Chemical Society.